Formulasi Briket Biorang Sekam Padi dan Biji Salak sebagai Sumber Energi Alternatif - Finta Amalinda; Muhammad Jufri (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2018)
Alternative energy can be produced from appropriate technology by utilizing biomass waste. For instance, rice husk and zalacca seeds which were by-product and waste that the benefits of has not been widely studied. The aim of this research is to find out the head value, duration of tima, ash and water contents, volatile matter, and carbon content of the mixture form of bio arangrice husk and zalacca seeds. This research is an experimental research which test was carried out in the laboratory. This research was conducted from June to august 2018. The object of this research is biomass formulation of bio arang mixtures of rice husk and zalacca seeds by mass comparison 0,25:1, 0,5:0,75, 0,5:0,5, 0,75:0,5 and 1:0,25 with the total mass of 200 gram, formed on the mold with a diameter of 5 centimeters, and a height of 7 centimeters. Based on the research, the result found that the mixed formulation of rice husk and zalacca seeds with ratio of 0,25:1 has the longest time duration which 38 minutes and 15 seconds, the largest water content approximately 5,761% and the highest carbon content was 60,326%. Furthermore, the mixed formulation of rice husk and zalacca seeds with ratio 1:0,25 has the highest heating value as much as 260,309 KJ/gr, the highest ash content was 13,829%, and the highest volatile matter substances was about 33,671%.Keywords : Briquettes , Bioarang , Rice husk biomass, Zalacca seeds